The Impact of Income Source and Taxpayer Citizenship on the Tax Burden Size - Kamarauskienė, Irma; Kazakevičiūtė, Erika (Buhalterinės apskaitos teorija ir praktika, 2024)
Recognition of professional qualifications and ensuring the free movement of workforce are among the measures for implementing sustainable development. The creation of quality jobs and economic growth in individual countries motivates residents to seek employment opportunities that match their professional qualifications and provides an incentive for citizens of other countries to integrate into the local labor market. A country's tax policy must be socially responsible to ensure fair taxation for all residents. If the tax burden is too high for certain population groups, it may encourage emigration or lead to labor shortages in specific sectors. A balanced tax policy can ensure long-term sustainability, reduce social inequality, and promote social stability. This article analyzes the taxation differences between Lithuanian and non-Lithuanian citizens who receive income from employment, active self-employment, and passive commercial activities. The aim is to determine whether these differences discriminate against citizens of different countries and restrict the free movement of labor. Additionally, the study calculates the tax burden, identifies the main factors influencing it, and formulates recommendations to reduce the impact of these differences.
Keywords: taxing burden; tax accounting; labor market equality